Efeito das oncoproteínas virais E6 e E7 do HPV-16 na resposta de células T de pacientes com carcinoma espinocelular de cabeça e pescoço - Soares, Gláucia Resende [UNESP] (2014)
The human papillomavirus (HPV) has been associated with squamous cell carcinoma (SCC) of the oropharynx, as a possible etiologic factor. The viral oncoproteins, E6 and E7 are able to inhibit the production of Th1 cytokines and initiate the production of Th2 cytokines, damaging the cellular response to infection. The purpose of this study is to evaluate the effect of viral oncoproteins E6 and E7 of HPV-16 on the response of T cells (CD4+ and CD8+) in patients with or without SCC of the head and neck. It was recruited for the study, 20 individuals, 10 patients with SCC of the head and neck and 10 individuals without cancer. To assess cell proliferation and cytokine release (TNF-α, IFN-γ, IL-2, IL-4 and IL-10) of CD4 and CD8 stimulation against synthetic peptides of the HPV-16 E6 and E7 genes, ELISA technique was used. The mapping of the HPV-16 DNA was performed in plasma and saliva samples by real time PCR. The results showed that the HPV-16 E7 peptide inhibited the production of cytokines by CD4 and CD8 T cells derived from subjects without cancer (6/10) and patients with SCC of the head and neck (5/10) (p <0, 05). The concavaline A protein induced proliferation of CD4 and CD8 T cells from individuals without cancer and patients with SCC of the head and neck (p <0.05). Cellular responses as to proliferative activity and cytokine production in patients with SCC of the head and neck were similar to the responses of individuals without cancer